Digital technologies in urban planning: a development vector for Uzbekistan (Международный научный журнал «Инженер», 2026)
In the context of the rapid development of digital technologies, urban planning design is becoming a key area for their implementation. The article examines modern digital tools, including building information modeling technologies (BIM), geoinformation systems (GIS), digital counterparts, and platform solutions used in international practice. Special attention was paid to analyzing the current state of digitalization in Uzbekistan's urban planning sector, identifying barriers and implementation prospects. A comparative analysis with foreign examples was conducted, and directions for the development of the national digital platform were proposed. The research results show that with comprehensive state support, personnel training, and the creation of a regulatory framework, Uzbekistan can accelerate the implementation of digital solutions in the architectural and construction industry, thereby increasing energy efficiency, sustainability, and the quality of the urban environment.